The Role of Drought Stress on Anther Culture of Wheat (Triticum aestivum L.) - Islam, S. M. Shahinul (Plant Tissue Culture and Biotechnology, 2010)
Drought stress was found to pose a significant effect on anther culture of wheat, namely Barkat, Kanchan and Pavon-76. Regeneration potentials of these varieties were determined by estimating the percentage of anther response, embryo induction, embryo regeneration and production of green and albino plants. It was observed that out of five treatments such as T1 (1 hr), T2 (3 hr), T3 (5 hr), T4 (7 hr) and T5 (9 hr) only T2 showed highest percentage of embryo yield and green plantlets. The T1 and T3 also gave significantly better results compared to the control. All the genotypes produced embryos and green plantlets and of them Barkat showed best performance followed by Kanchan and Pavon 76. Genotypes, under this study, produced green plants in addition to albinos but T4 and T5 showed three - fourfold higher albino plant production in comparison to treatments. Key words: Anther culture, Drought stress, Haploids, Triticum aestivum D.O.I. 10.3329/ptcb.v20i1.5965 Plant Tissue Cult. & Biotech. 20(1): 55-61, 2010 (June)